The Effect of Change Management in the Mujur Timber Sibolga Company (PT) on the Quality of Wood Processing into Plywood - Melsa Siagian; Nuri Aslami (Journal of Indonesian Management, 2022)
Change management is an approach to change individuals, teams, and organizations to a desired future state. The definition of change management is a process that takes place continuously to update the organization. This research was conducted to determine the extent of the performance carried out regarding the quality of making plywood at PT MUJUR TIMBER SIBOLGA. and the efforts made by employees for the production system, and analyzing the feasibility and stages of what processes are applied by employees at PT. Mujur Timber so that the processing of wood into plywood is of high quality.A company engaged in the processing of wood into plywood that was victorious in the 70s until 2006And PT. Mujur timber has greatly contributed to the improvement of the economy in the city of Sibolga, and Pt. Mujur timber is a company manufactures in the timber and forestry sector, is also an Export-oriented quality plywood company. As a labor-intensive company PT, Mujur timber This emphasizes the principle of Transparency.